(untitled) (Journal of Medicine, 2010)
15% of Tuberculosis patients have extra pulmonary lesions of which 1 to 3% have bone and joint lesions. In the musculoskeletal system, tuberculous spondylitis is most typical form of the disease; however, joint changes in extraspinal sites, such as the hip, knee, wrist & elbow, also may occur. Involvement of sternoclavicular joint is very rare. In 2 of the world’s largest series of osteoarticular TB, sternoclavicular joint involvement was reported in less than 0.5% of cases with less than 20 cases reported till date. However, with the emergence of drug resistant tuberculosis and large number of immunocompromised patients, the incidence may increase. We report a case of left sternoclavicular joint tuberculosis in an adolescent boy. As this entity is rare, level of suspicion is low and suspicion regarding TB arises only after poor response to antibiotic treatment. Early diagnosis and treatment is mandatory for good result Keywords: Tuberculosis, sternoclavicular joint, extrapulmonary tuberculosis DOI:10.3329/jom.v11i1.4286 J Medicine 2010: 11: 102-104